Mode Of Action Of Bhumyamalaki Churna In Asrigdara: A Critical Review - Rao, Sanju; Meemansa; Pushpalatha, B; Sonu (International Research Journal of Ayurveda & Yoga, 2020)
Abnormal uterine bleeding (AUB) is defined as any alteration in the pattern or volume of menstrual blood flow. The prevalence of AUB is very high i.e. 17.9% (FOGSI 2016/02/GRCP-ON-AUB) in present days. Abnormal uterine bleeding is one of the highly prevalent gynecological problems among the females during their reproductive years. Abnormal uterine bleeding or Asrigdara is of more concern, because excessive or prolonged bleeding may cause undue disruption of woman’s daily activities & affects woman’s health both physically and psychologically. The incidence rate of Asrigdara is increasing day by day, so if treatment is delayed this can lead to a worsening of the condition of the patient due to excessive blood loss.So, there is a great scope of research to find out safe, potent, cost effective remedy from Ayurveda by addressing the root of the problem thereby improving the quality of life of woman. Therefore many formulations have been mentioned in our texts for the treatment of Asrigdara.Yogaratnakar has described Bhumyamalaki Churna in the treatment of Pradara. Bhumyamalaki is Kapha Pittashamaka drug due to its properties like Sheetaveerya, Madhura Vipaka, Laghu-Ruksha Guna and Madhur, Tikta, Kasaya Rasa. It has anti-inflammatory and analgesic properties, which may influenced vascular apparatus of reproductive system. Bhumyamalaki is effective in Asrigdara due to its Raktapitta Shamaka and Yonidoshahara property. .